2007
DOI: 10.1037/0097-7403.33.4.371
|View full text |Cite
|
Sign up to set email alerts
|

The discrimination of natural movement by budgerigars (Melopsittacus undulates) and pigeons (Columba livia).

Abstract: Three experiments examined the ability of birds to discriminate between the actions of walking forwards and backwards as demonstrated by video clips of a human walking a dog. Experiment 1 revealed that budgerigars (Melopsittacus undulates) could discriminate between these actions when the demonstrators moved consistently from left to right. Test trials then revealed that the discrimination transferred, without additional training, to clips of the demonstrators moving from right to left. Experiment 2 replicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Of course, the latter introduces spatial complexities into the discrimination. As discussed by Koban and Cook (2009), one nice property of a rotation discriminations is that they eliminate such spatial confounds when dealing with motion (see also, Mui et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the latter introduces spatial complexities into the discrimination. As discussed by Koban and Cook (2009), one nice property of a rotation discriminations is that they eliminate such spatial confounds when dealing with motion (see also, Mui et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We have no evidence about whether or not the birds saw any kind of animal moving in Mui et al's (2007) video. Without evidence of correspondence in birds' eyes between the video and actual live humans and dogs, Mui et al (2007) should have resisted the temptation to anthropomorphize about their study, and the editor and reviewers should have found this obvious error. Of course without the tantalizing reference to natural movement, the study becomes much less interesting: all the more reason to work to avoid this anthropomorphic error.…”
Section: Avian Visual Science Without Correspondencementioning
confidence: 96%
“…Yet, we must warn readers to be alert to anthropomorphic errors in what might otherwise be useful research on basic processes. In a study of motion perception, Mui, Haselgrove, McGregor, Futter, Heyes, & Pearce (2007) successfully trained budgerigars and pigeons to discriminate video of a woman walking a dog either forwards or backwards in the same direction. Mue et al (2007) labeled their study one of discrimination of natural movement and discussed the work in terms of the ability of one animal to detection the movement of another.…”
Section: Avian Visual Science Without Correspondencementioning
confidence: 99%
“…Further evidence that input mechanisms can be specialized ontogenetically rather than phylogenetically comes from studies showing that monkeys (Klein, Deaner, & Platt, 2008), rats (Miller & Dollard,1941;Galef, 1981), budgerigars (Mui et al, 2007) honeybees (Dyer, Neumeyer, & Chittka, 2005), and humans (Behrens, Hunt, Woolrich, & Rushworth, 2008) become more attentive to social stimuli as a consequence of experience in which these stimuli provide reliable information about the availability and location of resources. The last of these studies is particularly interesting.…”
Section: Adaptive Specialization Of Input Mechanismsmentioning
confidence: 97%